2006
DOI: 10.1007/s10531-004-2937-4
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Diversity Indices – Modeling and Mapping Plant Biodiversity of Nallihan (A3-Ankara/Turkey) Forest Ecosystem in Frame of Geographic Information Systems

Abstract: Modeling and mapping possibilities of Shannon-Wiener, Simpson, and number of species (NS) indices were researched using geographic information systems (GIS) and remote sensing (RS) tools in Nallihan forest ecosystem of Turkey. The relationships between the indices and a number of independent variables such as topography, geology, soil, climate, normalized difference vegetation index (NDVI), and land cover were investigated to understand relationships between plant diversity and ecosystem. Georeferenced field d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 24 publications
0
12
2
Order By: Relevance
“…In contrast to studies of plant species richness in mountainous regions linking species richness and gradients in elevation (Dogan and Dogan 2006; Kumar and others 2006), we found no such relationship within the relatively flat Oak Openings region. However, for upland communities (especially sand barrens) we found a negative relationship between native species richness and measures of within-plot topographic heterogeneity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to studies of plant species richness in mountainous regions linking species richness and gradients in elevation (Dogan and Dogan 2006; Kumar and others 2006), we found no such relationship within the relatively flat Oak Openings region. However, for upland communities (especially sand barrens) we found a negative relationship between native species richness and measures of within-plot topographic heterogeneity.…”
Section: Discussioncontrasting
confidence: 99%
“…Spatial heterogeneity is hypothesized as one of the primary determinants of biodiversity (Huston 1994; Rosenzweig 1995), though the specific relationship between heterogeneity and diversity is often scale-dependent (Reed and others 1993; Tamme and others 2010). Recent studies evaluating a range of terrestrial ecosystems across multiple spatial scales have confirmed that relationships exist between plant species richness and various aspects of spatial heterogeneity, such as topography (Dogan and Dogan 2006; Dufour and others 2006; Thuiller and others 2006), landscape patch composition/configuration (Kumar and others 2006), soil depth (Lundholm and Larson 2003; Cingolani and others 2010), soil nutrients (Gilliam and Dick 2010), soil pH (Costanza and others 2011), water availability (Pausas and others 2003), grazing pressure (Olofsson and others 2008), and gradients in natural and human-caused disturbances (Deutschewitz and others 2003; Lilley and Vellend 2009). …”
Section: Introductionmentioning
confidence: 99%
“…As a result of the study, a distribution model with an explanation rate of 59% was obtained. When comparing the results of the studies done by Özkan and Berger (2014) and Dogan and Dogan (2006), the explained variance value of the distribution model obtained from the present study seems to be remained insufficient. One of the reasons of insufficiency of the distribution model we obtained is probably related to scale of the study area.…”
Section: Resultscontrasting
confidence: 69%
“…To build a distribution model of species diversity, the researchers used RTT, and reported the explained variance of the distribution model as 63%. Dogan and Dogan (2006) modeled plant species richness using by Simpson D diversity index with multiple regression analysis in The Nallıhan district of Turkey. As a result of the study, a distribution model with an explanation rate of 59% was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Several efforts have been made to map alpha diversity using variations in spectral reflectance data (Gould 2000; Palmer et al 2002; Rocchini et al 2004, 2007). Other studies employ combinations of predictive mapping and remote sensing through the application of empirical models on mixed datasets of environmental parameters, topography and reflectance (Ohmann & Gregory 2002; Cayuela et al 2006; Dogan & Dogan 2006).…”
Section: Introductionmentioning
confidence: 99%